Counseling on The Dangers of Early Marriage in an Effort to Prevent Stunting in Dobo Aru Islands - Nanlohy, Wildia; Bugis, Nova; Nurhidayati, Siti; Thalib, Abdul (CV. Paperhome Indonesia, 2024)
Early marriage, a practice that has been embedded in traditions for generations, has unpredictable and serious repercussions, especially in terms of health-related problems, such as pregnancy complications and stunted child growth. The purpose of this community service is to increase adolescent knowledge about early marriage and the risk of stunting. The results showed that counseling interventions were effective in increasing public knowledge about the dangers of early marriage and stunting. The proportion of individuals with good knowledge increased significantly after the extension program. These findings are consistent with previous research highlighting the effectiveness of education in changing behaviors related to early marriage and stunting. Conclusion, extension interventions have been shown to be effective in increasing knowledge about the dangers of early marriage and stunting. Continuous education efforts with appropriate methods and involving multistakeholders are essential to strengthen knowledge and encourage changes in community behavior